The importance of prophylaxis in surgical site infections - Piotrkowska, Renata; Książek, Janina; Wojciechowska, Elżbieta; Terech, Sylwia (Nursing Problems / Problemy Pielęgniarstwa, 2013)
Introduction. Surgical site infection is one of the most common complications in surgical patients. It contributes to an increased incidence, mortality, raises the cost of treatment and delays the recovery process. Therefore, application of prophylactic procedures relating to surgical site infections is of a significant value. The aim of the study is to evaluate the effect of prophylaxis in preventing surgical site infections in patients after traditional and laparoscopic cholecystectomy. Material and methods. The methodological aspect of the research was based on analysis of medical records and specialist literature. The Authors conducted a retrospective analysis of cases in which a traditional and laparoscopic cholecystectomy was performed. The area of research was the department of general surgery in one of Tri-city hospitals. Having received the hospital director’s permission, 40 patients hospitalised in 2012 were analysed. Results/Conclusions. The factor that contributed to surgical site infection in the study group was removing hair by means of an electric or manual razor. Regardless of a surgical method, no patient was protected with a sterile surgical gown.